B, N-Co-doped graphene quantum dots as fluorescence sensor for detection of Hg2+ and F− ions. Issue 14 (27th March 2019) - Yang, Panxing; Su, Jie; Guo, Ruiwei; Yao, Fanglian; Yuan, Caideng
Abstract : A novel fluorescence sensing platform based on boron and nitrogen co-doped graphene quantum dots (B, N-GQDs) was developed and used to detect the concentration of both Hg 2+ and F − ions. Abstract : Herein, we develop a fluorescence sensing platform based on boron and nitrogen co-doped graphene quantum dots (B, N-GQDs), which are synthesized by a one-step bottom-up hydrothermal method. The prepared B, N-GQDs exhibit high-fluorescence quantum yield (75%) and long fluorescence lifetime (12.86 ns). In the B, N-GQDs–Hg 2+ system, the fluorescence of B, N-GQDs is quenched with increasing Hg 2+ concentration due to the affinity interaction between the surface functional groups of B, N-GQDs and Hg 2+ . Subsequently, the quenched fluorescence of the B, N-GQDs–Hg 2+ system is gradually recovered with the addition of F − ions due to their strong affinity with Hg 2+ . The linear ranges for the detection of Hg 2+ and F − ions are 0.2–2.6 μM and 0.25–7.0 mM, respectively, and the detection limits are 0.16 μM and 0.18 mM for Hg 2+ and F − ions, respectively, which are below the regulatory level of 0.25 μM and 0.526 mM in the Integrated Wastewater Discharge Standard. Therefore, B, N-GQDs provide a facile and effective approach for the detection of both Hg 2+ and F − ions with real-time monitoring and high-speed measuring.